Household Wealth and Resilience to Financial Shocks in Italy - Garcia-Macia, Daniel (IMF Working Papers; Working Paper ;, 2018)
High household wealth is often cited as a key strength of the Italian economy. Both in absolute terms and relative to income, the Italian household sector is wealthier than most euro area peers. A sizable fraction of this wealth is held by the rich and upper middle classes. This paper documents the changes in the Italian household sector's financial wealth over the past two decades, by constructing the matrix of bilateral financial sectoral exposures. Households became increasingly exposed to the financial sector, which in turn was exposed to the highly indebted real and government sectors. The paper then simulates different financial shocks to gauge the ability of the household sector to absorb losses. Simple illustrative calculations are presented for a fall in the value of government bonds as well as for bank bail-ins versus bailouts.